2021
DOI: 10.1177/15327086211056575
|View full text |Cite
|
Sign up to set email alerts
|

To Vaccinate or Not? Decision-Making in the Time of COVID-19 Vaccines

Abstract: Decision-making has become an important component of the COVID-19 pandemic. A particular decision that we are currently presented with is whether to take up COVID-19 vaccines or not. Through the lens of autoethnography, I present my personal “vaccine decision-making” process as a social scientist who, despite having mixed emotions toward COVID-19 vaccines, made the decision to get vaccinated. Recognizing the subjective nature of my narrative, autoethnography is valuable to produce knowledge that is meaningful,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…This study highlighted that concerns about COVID-19 vaccine safety and effectiveness remain pervasive, even amongst those that are vaccinated. While these findings are congruent with several quantitative studies [ 48 , 49 ], qualitative data in this study revealed that these concerns centred around the perceived speed at which these vaccines were developed. The WHO declared a global pandemic in March 2020 [ 50 ]; by late 2020, there were already well over 200 vaccines under development and 40 vaccines in clinical trials [ 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study highlighted that concerns about COVID-19 vaccine safety and effectiveness remain pervasive, even amongst those that are vaccinated. While these findings are congruent with several quantitative studies [ 48 , 49 ], qualitative data in this study revealed that these concerns centred around the perceived speed at which these vaccines were developed. The WHO declared a global pandemic in March 2020 [ 50 ]; by late 2020, there were already well over 200 vaccines under development and 40 vaccines in clinical trials [ 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…Approaches to vaccine hesitancy should also consider addressing personal motivation and social influences as well as creating an enabling environment [ 22 , 54 , 55 ]. Most participants in our study believed that people who do not get the vaccine are taking risks both for their own health and that of the wider community.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine hesitancy is complex and context-specific and differs across time, place, and type of vaccines [ 20 ]. It has been strongly associated with lack of confidence in the safety and effectiveness of vaccines [ 21 , 22 ]. Moreover, the low perception of disease risk, also termed complacency, can also drive vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
“…Participant assent was obtained from all minors who participated in the study and all adult participants also provided consent for their participation and the use of transcripts. attention in South Africa [3,8]. COVID-19 vaccine hesitancy has been closely related to subjective and societal perceptions of vaccines and doubts in the efficacy of these vaccines [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to coping with the constantly evolving stressful reality of the pandemic, people were expected to make decisions about whether they wanted to receive a COVID-19 vaccine or not [ 3 ]. Global vaccination was considered a priority to reduce the spread of the coronavirus and to achieve herd immunity [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%